SATIRE IN THE DAILY SHOW TWITTER ACCOUNT - YOGI ASRAF; SRI MINDA MURNI (State University of Medan, 2022)
This study was conducted to uncover the aspects related to satire in The Daily Show Twitter account. The data of this research included 40 tweets selected during the 2020 US presidential election. The researcher used descriptive qualitative in analyzing the data. The data in this research were collected by using recorder technique and documentary sheet as the instrument to collect the data. The purpose of this study were (1) to find out the types of satire (2) to describe the realization of satire, and (3) to explain the reason for the use of satire. Based on the result of this study, there were three types of satire with the total of horatian 52,5%, juvenalian 17,5%, and manippean 30%. Besides, there were seven satirical techniques found in the tweets namely irony, paradox, antithesis, enlargement, anticlimax, exaggeration, and parody. Furthermore, satire in the tweets were used to be humorous, criticize politicians, and inform the audience about political topics.